Family Shocks and Academic Achievement - Marie C. Hull (Institute for the Study of Labor (IZA), 2015)
Disruptions in family life can take many forms, but all have the potential to impact student learning. With school administrative data matched to birth records, I estimate the effect of unexpected changes in the home environment, or family shocks, on achievement. Identification comes from siblings observed in the same year. I find that family shocks are at least as important as teacher assignment for student learning. Furthermore, they have a relatively larger impact on students from affluent families; time use evidence indicates that this is likely because affluent parents are more involved in their children's learning.
Keywords: J24; I21; I24; 330; education; human capital; family dynamics; educational inequality; time inputs